Aulіn V., Tikhii A. Influence of condition changing and properties of soil on deterioration of working organs, which are working at different operating depth. - Аулін, В.В.; Тихий, А.А. (Problems of Tribology, 2014)
The changes of state of the environment during processing soil by working organs of tillage machines. It is shown that the individual phases of soil differently resist WOTM of force and influence on the deformation of the soil. The dependence of the wear patterns and the working bodies of the density of the solid phase in the soil moisture content and porosity of the soil environment. The effect of changes in the state and properties of the soil on the wear of the working bodies of tillage machines operating at different depths. Found that, in the long process of agricultural cropland soil is compacted with a deep and regimental treatments. Were used for such as WOTM of sliter and unilateral flat paw. Soil porosity changes with less flat processing compared to processing at different depths. Increase in the density of lumps that may form during processing, is due to the fact that in the process of interaction with the soil WOTM in the lower forms the core compaction. The core of compaction and compacted soil are key to the formation of the working surface of compacted clods and the local area, which adds to the crumbling of the soil, and thus the cost of additional energy. The distribution of stress with distance from the working surface of the foot and one-sided sliter in surface soils adjacent to the working surfaces WOTM. Studies have shown that the value of the distribution of stress in the soil with the distance from the working surface WOTM depend both on the type of WOTM and depth of topsoil. Results of the study the size and nature of the standard one-sided wear pads and a circular stand sliters show their dependence on the type of soil, their properties and characteristics, and the ratio of the phase components of the stress distribution in the soil. Proved that the porosity of the soil is an influential factor that significantly alters the wear CE WOTM. This relationship suggests that the choice of type of treatment should take into account the porosity of the soil, and therefore its previous treatment. The regularity of wear CE WOTM changes the density of the solid phase at a fixed moisture content, that is, there is an exponential dependence of the wear decrease with decreasing density of the solid soil.